F I S T - SciTEXS creative & innovative annual challenge - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Siti Maznah, Kabeb; Noor Suhana, Adzahar (Penerbit UMP, 2010)
Gambang, March 25 - FIST in collaboration with the Science Technology Expert Society (SciTEXS) held a Creative & Innovative Annual Challenge. Eleven groups comprising 57 Industrial Chemistry and Industrial Biotechnology students participated. Science-based projects with practical applications were conceptualized under the guidance of lecturers at FIST. On hand to launch the Challenge was t he Dean. The group, "Aqua Touch'; won first place, followed by "Hot Ice" and "B.U.S.T.E.R."